2011
DOI: 10.1007/s11242-011-9804-z
|View full text |Cite
|
Sign up to set email alerts
|

Forward and Inverse Bio-Geochemical Modeling of Microbially Induced Calcite Precipitation in Half-Meter Column Experiments

Abstract: Microbially induced calcite precipitation (MICP) offers an alternative solution to a wide range of civil engineering problems. Laboratory tests have shown that MICP can immobilize trace metals and radionuclides through co-precipitation with calcium carbonate. MICP has also been shown to improve the undrained shear response of soils and offers potential benefits over current ground improvement techniques that may pose environmental risks and suffer from low "certainty of execution." Our objective is to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(51 citation statements)
references
References 33 publications
1
50
0
Order By: Relevance
“…MICP process monitoring is exemplified through results from one-dimensional column experiments (length ¼ 45 cm, diameter ¼ 5 cm) performed on sand (D 50 ¼ 0.21 mm) to improve spatial uniformity (figure 6a) [84]. Similar approaches have been reported by Whiffin et al [85].…”
Section: Process Monitoring Of Experimentsmentioning
confidence: 70%
“…MICP process monitoring is exemplified through results from one-dimensional column experiments (length ¼ 45 cm, diameter ¼ 5 cm) performed on sand (D 50 ¼ 0.21 mm) to improve spatial uniformity (figure 6a) [84]. Similar approaches have been reported by Whiffin et al [85].…”
Section: Process Monitoring Of Experimentsmentioning
confidence: 70%
“…Ureolysis driven MICP involves a microbially catalyzed reaction, which can be modeled if the reaction kinetics are known (Burbank et al, ; Chahal et al, ; Krajewska, ; Mobley & Hausinger, ). Models for predicting MICP processes have been developed by a number of authors (Barkouki et al, ; Cuthbert et al, ; Ebigbo et al, ; Martinez et al, ; van Wijngaarden et al, ). The different models reported have focused on addressing complexities in the different interacting processes and often are designed to match a series of experiments usually at small scales.…”
Section: Introductionmentioning
confidence: 99%
“…1); -inverse first-order distribution, as proposed by Barkouki et al (2011), which corresponds to a change of the direction of flow after inoculation. Barkouki et al (2011) propose that this distribution of cells will lead to a more homogeneous distribution of precipitated calcite, as the reduction of reactants along the flow path is counteracted by an increase in catalyzing enzyme. Even though this initial biomass distribution is likely to be unrealistic for subsurface applications, it provides an upper bound on how much the resulting calcite precipitation can be influenced by the initial biomass distribution.…”
Section: Initial Biomass Distributionsmentioning
confidence: 99%
“…It has been suggested that the distribution of cells in the porous medium during MICP is a key parameter (Barkouki et al 2011). Yet it is very difficult to control or even reliably measure the concentrations of attached microbial cells (e.g., Bouwer et al 2000;Cunningham et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation